Efek Self Efficacy sebagai Variabel Moderasi pada Pengaruh Job Insecurity terhadap Organizational Citizenship Behavior - Cindy Larasati; Tona Aurora Lubis; Agus Sholikhin (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
Research entitled The Effect of Self Efficacy as a Moderating Variable on the Influence of Job Insecurity on Organizational Citizenship Behavior. The purpose of this study aims to test and analyze the effect of Self Efficacy to moderate the effect of Job Insecurity on Organizational Citizenship Behavior (OCB) and Job Insecurity on Organizational Citizenship Behavior (OCB). The research method used is quantitative descriptive analysis with the Structural Equation Modeling (SEM-PLS) model using SmartPLS. Based on the results of the study, it shows that the effect of Job Insecurity on Organizational Citizenship Behavior (OCB) produces positive and significant results. The effect of Self Efficacy on the effect of job insecurity on Organizational Citizenship Behavior (OCB) is positive and significant. Self Efficacy for non-ASN Personnel in the form of belief in one's own ability to be able to influence the life of the individual itself, in this case job insecurity owned by non-ASN Staff is able to strengthen the effect of job insecurity on Organizational Citizenship Behavior (OCB).